DEFINITION OF KEY TYPES OF PROFESSIONAL TRAINING OF POLICE OFFICERS IN UKRAINE (Bulletin of criminological association of Ukraine, 2023)
Attention is drawn to the fact that the general task of training in higher education institutions with specific training conditions is to provide those knowledge, abilities, and skills that correspond to the established characteristics of a certain educational and qualification level, which is confirmed by the police officer receiving a diploma of the established model. It is noted that the types of professional training of police officers are the result of the differentiation of professional training according to various criteria that reflect its most significant characteristics. The latter are proposed to be divided: a) by target levels: 1) initial acquisition of the minimum amount of knowledge and skills to perform basic functional tasks of the police (primary professional training); 2) obtaining education as a means of mastering a certain educational and qualification level of a certain specialty, which will allow performing those police service and labor functions that require a certain degree of education at a professional level (training in higher education institutions with specific training conditions); 3) improving the professional knowledge and skills of current police officers to increase the success of their performance of official duties (postgraduate education, as well as in-service training); b) by areas of influence on the professional skills of police officers: intellectual (in particular, improving legal knowledge, document management skills, etc.); physical (development of physical capabilities, improving the implementation of physical standards); ethical (development of communication skills based on respect for the rights, freedoms, honor and dignity of each person on an anti-discriminatory basis); special police (skills in handling special means and firearms).
Keywords: classification; types; professional training; police officers; National Police